2013
DOI: 10.3892/ijmm.2013.1376
|View full text |Cite|
|
Sign up to set email alerts
|

COX-2 regulates E-cadherin expression through the NF-κB/Snail signaling pathway in gastric cancer

Abstract: Cyclooxygenase-2 (COX-2) participates in cancer invasion and metastasis by decreasing the expression of E-cadherin. However, the molecular mechanisms through which COX-2 regulates E-cadherin expression and function have not yet been fully elucidated. The aim of this study was to investigate the possible molecular mechanisms through which COX-2 regulates E-cadherin expression in gastric cancer. The mRNA and protein expression of COX-2, nuclear factor-κB (NF-κB), Snail and E-cadherin was detected in gastric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 25 publications
4
40
0
Order By: Relevance
“…In breast cancer, NF-κB also suppresses E-cadherin levels by inducing the expression of the master regulators Snail, Slug, ZIB1, ZIB2 and Twist [61]. Interestingly, the increased expression of NF-κB and Snail observed in gastric cancer tissues, coincides with a considerable reduction in E-cadherin levels in the cancer tissues compared to the normal gastric mucosa [62]. …”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, NF-κB also suppresses E-cadherin levels by inducing the expression of the master regulators Snail, Slug, ZIB1, ZIB2 and Twist [61]. Interestingly, the increased expression of NF-κB and Snail observed in gastric cancer tissues, coincides with a considerable reduction in E-cadherin levels in the cancer tissues compared to the normal gastric mucosa [62]. …”
Section: Discussionmentioning
confidence: 99%
“…Our results 1677 1678 1679 1680 1681 1682 1683 1684 1685 1686 1687 1688 1689 1690 1691 1692 1693 1694 1695 1696 1697 1698 1699 1700 1701 1702 1703 1704 1705 1706 1707 1708 1709 1710 1711 1712 1713 1714 1715 1716 1717 1718 1719 1720 1721 1722 1723 1724 1725 1726 1727 1728 1729 1730 1731 1732 1733 1734 1735 1736 demonstrated that the regulation of Cox-2 via Nf-kB pathway was involved in the inflammatory signaling of KIC in rat urinary bladder. Findings from a previous study in gastric cancer suggested that COX-2 activates NF-kB, thus regulating the transcription and expression of E-cadherin through the SNAI1 signaling pathway in gastric cancer, 42 and that COX2emediated down-regulation of E-cadherin was dependent on the NF-kB pathway. 43 Blockade of COX-2 activity, either by COX-2 siRNA or celecoxib, restored the expression of E-cadherin.…”
Section: Role Of Cox-2 In Bladder Overactivity and Altered Micturitiomentioning
confidence: 97%
“…COX-2 mediates production of thromboxane B2 and prostaglandins in gastric cancer cells, which promote cell proliferation and macrophage infiltration in stomach tissue [85]. Prostaglandins regulate NF-κB signaling by a positive feedback loop, which further amplifies and maintains inflammatory process and promotes formation of new blood vessels in tumor site [86,87]. …”
Section: Pro-inflammatory Mediators and Growth Factors In The Gastmentioning
confidence: 99%